HUBUNGAN PENGGUNAAN SMARTPHONE TERHADAP KEMAMPUAN KOGNITIF ANAK USIA SEKOLAH - Sari Dewi Mareta; Juniar " Ernawaty; Nurul " Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Technology is an important thing in our daily life to do social activity and to communicate with other people. As the technology develop faster, smartphone put in appearance. Not only adults are using smartphones but also school-aged children. Childrens that use smartphones wisely, they will get good cognitive ability. This research aimed to determine the correlation between using smartphones and school-aged children’s cognitive ability. The design of this research was descriptive correlational with cross sectional approach. Study was conducted in SDN 039 Pekanbaru with 140 samples were selected using stratified random sampling technique. This research used questionnaire that has been validity and realibility tested. The analysis use were univariat analysis to find the frequency distribution and bivariat analyses using chi-square test. The result showed that there was correlation between using smartphones and school-aged children’s cognitive ability with p value (0,000) < α (005). Parents should control their school-aged children’s from negative ways of using smartphone. Keywords: School-aged children, cognitive ability, smartphones use